A Semiotic Study of One Ready-To-Drink Tea Billboard Advertisement in Jakarta - Anna Marietta da Silva (Lingua Cultura, 2017)
The purpose of this research was to delve into the linguistic and non-linguistic aspects of a pioneer brand of bottled green tea in the Indonesian market. Four main aspects of the Semiotics study, namely the represented participants, modality, composition, and interactive participants were used to analyze the advertisement. The data for this research was a billboard of Nü Green Tea that was placed in Jl. Kasablanka Raya in South Jakarta. The findings show that the interplay between the non-human object, play of colors, composition, and language choice has been designed carefully in order to boost the targeted audience’s attention to the product.